New phytotelmic habitat of Metriocnemus eryngiotelmatus (Diptera: Chironomidae) - Siri, Augusto (2008)
This is the first report of the non-biting midge Metriocnemus eryngiotelmatus Donato & Paggi 2005 associated to the impounded water of Dipsacus fullonum L. plants.